A novel vaccine strategy employing serologically different chimpanzee adenoviral vectors for the prevention of HIV-1 and HCV coinfection - Gardiner, Clair; Hartnell, Felicity; Brown, Anthony; Capone, Stefania; Kopycinski, Jakub; Bliss, Carly; Makvandi-Nejad, Shokouh; Swadling, Leo; Ghaffari, Emma; Cicconi, Paola; Del Sorbo, Mariarosaria; Sbrocchi, Roberta; et al. (My University, 2019)
Background: Nearly 3 million people worldwide are coinfected with HIV and HCV. Affordable strategies for prevention are needed. We developed a novel vaccination regimen involving replication-defective and serologically distinct chimpanzee adenovirus (ChAd3, ChAd63) vector priming followed by modified vaccinia Ankara (MVA) boosts, for simultaneous delivery of HCV non-structural (NSmut) and HIV-1 conserved (HIVconsv) region immunogens. Methods: We conducted a phase I trial in which 33 healthy volunteers were sequentially enrolled and vaccinated via the intramuscular route as follows: 9 received ChAd3-NSmut [2.5 × 1010 vp] and MVA-NSmut [2 × 108 pfu] at weeks 0 and 8, respectively; 8 received ChAdV63.HIVconsv [5 × 1010 vp] and MVA.HIVconsv [2 × 108 pfu] at the same interval; 16 were co-primed with ChAd3-NSmut [2.5 × 1010 vp] and ChAdV63.HIVconsv [5 × 1010 vp] followed at week 8 by MVA-NSmut and MVA.HIVconsv [both 1 × 108 pfu]. Immunogenicity was assessed using peptide pools in ex vivo ELISpot and intracellular cytokine assays. Vaccine-induced whole blood transcriptome changes were assessed by microarray analysis. Results: All vaccines were well tolerated and no vaccine-related serious adverse events occurred. Co-administration of the prime-boost vaccine regimens induced high magnitude and broad T cell responses that were similar to those observed following immunization with either regimen alone. Median (interquartile range, IQR) peak responses to NSmut were 3,480 (2,728–4,464) and 3,405 (2,307–7,804) spot-forming cells (SFC)/106 PBMC for single and combined HCV vaccinations, respectively (p = 0.8). Median (IQR) peak responses to HIVconsv were 1,305 (1,095–4,967) and 1,005 (169–2,482) SFC/106 PBMC for single and combined HIV-1 vaccinations, respectively (p = 0.5). Responses were maintained above baseline to 34 weeks post-vaccination. Intracellular cytokine analysis indicated that the responding populations comprised polyfunctional CD4+ and CD8+ T cells. Canonical pathway analysis showed that in the single and combined vaccination groups, pathways associated with antiviral and innate immune responses were enriched for upregulated interferon-stimulated genes 24 h after priming and boosting vaccinations. Conclusions: Serologically distinct adenoviral vectors encoding HCV and HIV-1 immunogens can be safely co-administered without reducing the immunogenicity of either vaccine. This provides a novel strategy for targeting these viruses simultaneously and for other pathogens that affect the same populations. Clinical trial registration: https://clinicaltrials.gov, identifier: NCT02362217
Keywords: HIV-1; Hepatitis C; Vaccine; Coadministration; Clinical trial; Conserved region; Non-structural protein; Transciptomics analysis